Investigating the brand equity strategy of halal food in a promising emerging Islamic market in a non-Muslim country - Pattareya Sungnoi; Vuttichat Soonthonsmai (Cogent Business & Management, 2024)
This research study highlighted the factors that influence the brand equity strategy of halal food products. In this study, the researchers have chosen to address the gap in the literature pertaining to non-majority Muslim country. The study aimed to identify the influence of consumer behavior, marketing strategies, integrated marketing communication, and added value on halal food brand equity in Thailand. A quantitative study was conducted using a structural equation model by LISREL. Data were collected through online questionnaires and personal interviews with 460 Muslim consumers residing in Thailand. Quota sampling was employed for each province, and descriptive statistics and structural equation modeling analysis were performed. The empirical data was consistent with the causal relationship model. Brand equity was directly influenced by added value and indirectly influenced by consumer behavior and marketing strategy, while integrated marketing communication influenced it through added value.
Keywords: 650; Marketing strategy; brand equity; halal food; new emerging Islamic market